Increasing Speech Building Abilities for Children with Hearing Impairment - Heavy Evasari; Mohammad Efendi; Henry Praherdhiono (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Students with hearing impairment  have difficulty in hearing due to stiffness in speak organs so that their communication is hindered. The purpose of this research is to increase basic communication skill that is speech building. This research is quasi-experiment using interrupted time series design. The result showed that the value increased by 31,92 from 42,92 in pre-test to 74,88 in post-test. Intervention was in the form of prompting with reinforcement for motivating students. It is concluded that prompting technique significantly  increases the speech building ability of students with hearing impairment. Teachers are suggested to use this technique as an alternative for increasing children communication skill.